Pengaruh Payment Gateway dan Kemudahan Transaksi Terhadap Keputusan Pembelian Dengan Etika Konsumsi Islam Sebagai Variabel Moderasi: Studi Kasus Produk Mukenah Dalanova, Widiping - Azmil Mustaqor; Sujoko Winanto (Peneliti.net, 2022)
The Technological developments makes changes affect for consumption level of a Muslim woman with the existence of non-cash payment methods that use payment gateways that can provide various transaction conveniences and in fact can be detrimental to users. This study aims to determine the effect of payment gateways and ease of transactions on purchasing decisions with Islamic consumption ethics as a moderating variable. The population in this study are consumers who buy Mukenah Dalanova products at Widiping payment gateway users (OVO, Gopay, Flip, Dana, Research testing using instrument testing with structural equity modeling (SEM) analysis. The results obtained from this study have several findings indicating that: (1) there is a negative and significant effect of payment gateway on purchasing decisions on products (2) there is a positive and significant effect of ease of transaction on purchasing decisions (3) there is a positive and significant influence of Islamic consumption ethics on purchasing decisions on Mukenah Dalanova products, Widiping (4) there is a negative and significant influence si There is a significant negative and significant influence of Islamic consumption ethics as a moderating variable between transaction convenience and purchasing decisions on Mukenah Dalanova, Widiping products.